Global Perspectives on School–University Partnerships Between and Within Countries - Goodwin, A. Lin; Pratt, Suzanne (Cambridge University Press, 2026)
In the context of an ever-shrinking world, where education concerns are shared across borders, and the 2030 deadline to achieve the 17 United Nation Sustainable Development Goals – specifically goal 4: “inclusive and equitable quality education … for all” is looming, it seems timely to take a look at school-university partnerships from a global perspective. This chapter begins with a quick scan of school-university partnerships, primarily in the US. It then examines school-university partnerships in – or with – other parts of the world, using available – and accessible – literature. What are some examples of school-university partnerships across different countries and what kinds of conversations frame this phenomenon? It closes by discussing some enduring issues that plague school-university partnerships and suggest how global collaborations might generate new insights into perennial problems.
The Cambridge Handbook of School–University Partnerships